The use of Declaration of Illocutionary Acts of the Korean-English Drama “I Hear Your Voice” - Endang Sartika; Sari Marzuqoh; Khoirul Majid (Journal of Pragmatics Research, 2019)
This study deals with the types of declaration of illocutionary acts in the Korean-English Drama “I Hear Your Voice”. The objectives of this study are (1) to find and classify the utterances in the English subtitle of the Korean drama entitled “I Hear Your Voice” that belongs to declaration of illocutionary acts, (2) to analyze the implication of the declaration of illocutionary act found in the Korean English drama “I Hear Your Voice”. This research applies descriptive qualitative method. The objects of this study are English Subtitles of the drama in episode 8 to 13 which is containing the utterances of Declaration of Illocutionary Acts. The researcher found 40 declaration of illocutionary act utterance which is divided into five types of Declaration of Illocutionary acts and the dominant types was Sentencing. For specific result, the researcher provided the percentage in detail; Resigning (5%) in 2 data, Demising (12,5%) in 5 data, Naming (17,5%) in 7 data, Appointing (20%) in 8 data, and Sentencing (45%) in 12 data. The implication of the result of this research toward English Language Teaching is that this research could be authentic material by teachers or lecturers to teach Pragmatic especially about Speech Acts.Key words: Declaration, Illocutionary acts, Speech acts.